PENGARUH KREDIT TERHADAP PERTUMBUHAN EKONOMI INDONESIA TAHUN 1980-2011 - ME, ROMI SURADI (Jurnal Ekonomi Daerah (JEDA), 2013)
ABSTRACT Economic development of a country depends on the development of dynamic and real contribution of the banking sector. One of the main activities of the banking sector is lending to the public. Therefore, the banking sector has a fundamental role in the economy and people's lives. This study tried to analyze the effect of consumer credit, working capital and investment to Indonesia's economic growth by using ordinary least squares (OLS). This study aims to see how they affect consumer credit, working capital and investment to economic growth using time series data from the years 1980 to 2011. This study uses a computer program E-Views. The data used in this study is secondary data analysis of the data and the model in the form of multiple regression. The results showed that the coefficient of determination is approximately 50.88% 0,508874 That is influenced by changes in economic growth determinant variables in the model while the remaining 49.12% is explained by other variables not included in the model estimation. F-statistics is greater than the F-table (9,670617 > 2.95) which means that the consumer credit, working capital and investment are jointly significant effect on economic growth in Indonesia at 95% confidence level. Keyword: Economic Growth, Credit Consumption, Working Capital, Investment.